Chitosan, chitosan derivatives, and chitosan-based nanocomposites: eco-friendly materials for advanced applications (a review) - El-Araby, Abir; Janati, Walid; Ullah, Riaz; Ercisli, Sezai; Errachidi, Faouzi (Frontiers in Chemistry, 2024)
For many years, chitosan has been widely regarded as a promising eco-friendly polymer thanks to its renewability, biocompatibility, biodegradability, non-toxicity, and ease of modification, giving it enormous potential for future development. As a cationic polysaccharide, chitosan exhibits specific physicochemical, biological, and mechanical properties that depend on factors such as its molecular weight and degree of deacetylation. Recently, there has been renewed interest surrounding chitosan derivatives and chitosan-based nanocomposites. This heightened attention is driven by the pursuit of enhancing efficiency and expanding the spectrum of chitosan applications. Chitosan's adaptability and unique properties make it a game-changer, promising significant contributions to industries ranging from healthcare to environmental remediation. This review presents an up-to-date overview of chitosan production sources and extraction methods, focusing on chitosan's physicochemical properties, including molecular weight, degree of deacetylation and solubility, as well as its antibacterial, antifungal and antioxidant activities. In addition, we highlight the advantages of chitosan derivatives and biopolymer modification methods, with recent advances in the preparation of chitosan-based nanocomposites. Finally, the versatile applications of chitosan, whether in its native state, derived or incorporated into nanocomposites in various fields, such as the food industry, agriculture, the cosmetics industry, the pharmaceutical industry, medicine, and wastewater treatment, were discussed.